The effect of housing temperature and a high-fat, high-carbohydrate diet on maternal interscapular brown adipose tissue - AlHarethi, Enas (2019)
Brown adipose tissue (BAT) has a role in energy balance and the utilization of fatty acids and glucose, but the extent to which its composition may be modulated by housing temperature is unknown, especially during gestation. BAT activity decline during gestation to enable conservation of maternal energy. This study aimed to investigate the effect of the standard housing temperature (20°C) as compared to a thermoneutral environment (~27°C) on obesity during gestation. The hypothesis is the impact of gestation and high-fat, high-sucrose (HFHS) diet on BAT and white adipose tissue (WAT) would be pronounced on thermoneutral temperature conditions and these changes would be mediated by changes in BAT.